โปรแกรมทางผ่านสำหรับระบบห้องสมุดซีดีรอมเชิงเลขในเครือข่าย - ศานิต วิรยศิริ (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
This thesis presents a design and development of gateway programs for CD-ROM digital library services over network. These programs operate as World Wide Web services in the Internet using standard Common Gateway Interface (CGI) and remote access techniques. There are two types of CD-ROMs supported in the system, data file CD-ROMs and database application CD-ROMs. The system provides additional services such as searching, personal bookshelf, calculating usage statistics, and CD-ROM management utilities for the library. Experimental results showed that the average number of requests is approximately 30.02% of the number of requests obtained from a CGI program that directly read target files and 18.08% of the number of requests obtained from direct request from the web server.